Implementation of tele-geriatricmental healthcare for rural veterans: factors influencing care models - Gould, Christine E.; Paiko, Lynsay; Carlson, Chalise; Humber, Marika Blair; Trivedi, Ranak; Filips, Julie; Savell, A. Denise; Lloyd, Althea; Peeples, Amanda D. (Frontiers in Health Services, 2024)
IntroductionAging rural veterans have limited access to geriatric mental health services. The establishment of Veterans Health Administration (VHA) regional telehealth hubs, or Clinical Resource Hubs (CRHs), has the potential to improve access to specialist care via telehealth delivered across healthcare systems within each VHA region. We used the Consolidated Framework for Implementation Research (CFIR 1.0) to examine variations in the tele-geriatric mental health (tele-GMH) care models being used in four CRHs.MethodsWe interviewed 11 CRH geriatric mental health providers and 12 leaders to (1) characterize the models of care, (2) identify factors in their region that support tele-GMH, (3) identify factors underlying model adaptations, and (4) learn about barriers and facilitators during implementation. The interviews were analyzed using a combination of CFIR-based coding and rapid qualitative analysis.ResultsThe services used multiple telehealth modalities; their care delivery approach ranged from consultative to continuity services. Aspects of the inner setting, specifically structural characteristics, implementation climate, and implementation readiness, influenced the model that each CRH implemented. Barriers were largely related to inner setting structural characteristics. Facilitators highlighted the importance of planning, iteration, and engaging stakeholders during implementation.ConclusionTele-GMH models varied in approach, tailoring their services to fit inner setting characteristics. Barriers and facilitators remained consistent across regions. Attending to inner setting characteristics, ongoing process improvement, and nurturing relationships with stakeholders is critical throughout the implementation of a tele-GMH program. Future research should examine the impact of the varied care delivery models on quantitative outcomes, including metrics related to access and healthcare utilization.